Biobutanol – An impending biofuel for future: A review on upstream and downstream processing tecniques. (February 2017) - Bharathiraja, B.; Jayamuthunagai, J.; Sudharsanaa, T.; Bharghavi, A.; Praveenkumar, R.; Chakravarthy, M.; Yuvaraj, D.
Abstract: Driven by the increase in industrialization and population, the global demand for energy and material products is steadily growing. Since the world primary sources for energy and chemicals are fossil fuels, this growth raises significant issues at environmental, economic and social levels. To meet the increasing demand of energy sources, biomass resources are extremely promising. For the sustainable production of renewable energy, the production of biobutanol through ABE fermentation was investigated by upstream and downstream processing techniques. ABE fermentation was achieved using Clostridium species whose genes help in the conversion of biomass into butanol. Further, genetic engineering techniques are used to modify these organisms to increase the yield of butanol. Biobutanol is found to be efficient fuel compared to other known biofuels both by physical and chemical properties. In order to accomplish the increasing demand of this fuel; selection of species, identification of subtrates, pre-treatment, genetic engineering techniques and various downstream processing techniques (pervaporation, gas stripping, etc.) are inculcated which are been discussed in this review. This review also focuses on economics of biobutanol across the globe.